2019
DOI: 10.5935/1984-0063.20190064
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as a favorable non-pharmacologic treatment to Sleep-Related Movement Disorders: a review

Abstract: Non-pharmacologic treatments of Sleep-Related Movement Disorders (SRMD) are already well described in the literature. The physical activity has been presented as a factor to improve quality of life and in several aspects related to sleep disorders. Thus, the purpose of this review was to analyze the benefits of physical exercise and your indication to improve to SRMD. In the research, 19 studies were found that evaluate the efficacy of physical exercise on SRMD in both human and animal models. The results demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Physical activity increases the secretion of beta-endorphin, as an endogenous opioid, which is produced by the anterior pituitary and endorphins in the nervous system [36][37][38]. Beta-endorphin leads to analgesia by binding to pre-and post-synaptic opioid receptors [39].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity increases the secretion of beta-endorphin, as an endogenous opioid, which is produced by the anterior pituitary and endorphins in the nervous system [36][37][38]. Beta-endorphin leads to analgesia by binding to pre-and post-synaptic opioid receptors [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although these processes may prevent the occurrence of PLMS, the mechanisms involved are not yet fully understood. The study by Franco et al [24] also reports that increased levels of dopamine, following physical activity, have a similar effect on the body as dopaminergic agonists, medications that are commonly used in the pharmacological treatment of PLMS.…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, in another randomized trial, Harrison et al [23] found no significant effects on RLS symptoms of a so-called tension and trauma release exercise program, conducted once a week over a period of six weeks (n = 9 participants in each group). The work of Franco et al [24] suggests that physical exercise is a favorable non-pharmacological treatment for sleep-related movements disorders including RLS; regarding the potential mechanisms involved, the authors presume that exercise causes the release of beta-endorphins, which interact with opioid receptors in the brain, and dopamine, which leads to neurochemical balance in the brain. Although these processes may prevent the occurrence of PLMS, the mechanisms involved are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in another randomized trial Harrison et al (19) did not nd a signi cant effect of a program of so-called tension and trauma release exercises once a week over a period of six weeks (n = 9 participants in each group). Franco et al (20) suggested that physical exercise is a favorable non-pharmacological treatment for sleep-related movements disorders including RLS. Therefore, the question arises whether individuals with idiopathic RLS also bene t from daily physical activity with regard to their sleep quality during the following night.…”
Section: Introductionmentioning
confidence: 99%